2010
DOI: 10.1097/pec.0b013e3181c399df
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a Marker of Severe Bacterial Infection in Children in the Emergency Department

Abstract: Procalcitonin, the prohormone of calcitonin, is a relatively new and innovative marker of bacterial infection that has multiple potential applications in the pediatric emergency department. In healthy individuals, circulating levels of procalcitonin are generally very low (<0.05 ng/mL), but in the setting of severe bacterial infection and sepsis, levels can increase by hundreds to thousands of fold within 4 to 6 hours. Although the exact physiologic function of procalcitonin has not been determined, the consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 121 publications
2
23
0
Order By: Relevance
“…WBC is one of the commonly seen inflammatory markers in clinics. In pathological state, WBC level can show a remarkable increase or decrease due to different immunoreactions states and pathogenic bacteria, both of which indicated systemic bacterial infection 11,12. CRP level is one of the frequently used indexes for the diagnosis of infection currently in China 13.…”
Section: Discussionmentioning
confidence: 99%
“…WBC is one of the commonly seen inflammatory markers in clinics. In pathological state, WBC level can show a remarkable increase or decrease due to different immunoreactions states and pathogenic bacteria, both of which indicated systemic bacterial infection 11,12. CRP level is one of the frequently used indexes for the diagnosis of infection currently in China 13.…”
Section: Discussionmentioning
confidence: 99%
“…One study (109) demonstrated that different biomarkers had varying ability to predict subsequent sepsis; IL-6 performed better than PCT, which performed better than CRP. However, another study (110) found no significant difference in the IL-6 plasma levels of postoperative patients who developed SIRS compared with those who did not, but it did find that the ratio of TNF to IL-10 was predictive.…”
Section: Biomarkersmentioning
confidence: 99%
“…For example, levels of PCT are increased in typical, but to a lesser extent, atypical, pneumonia 46. Infections associated with Gram-negative bacteria also cause a greater elevation in PCT levels compared with Gram-positive infections47 as do some viral or fungal infections 48…”
Section: Limitations Of Pctmentioning
confidence: 99%